Heart Plasticity in Response to Pressure- and Volume-Overload: A Review of Findings in Compensated and Decompensated Phenotypes - Pitoulis, Fotios G.; Terracciano, Cesare M. (Frontiers in Physiology, 2020)
The adult human heart has an exceptional ability to alter its phenotype to adapt to changes in environmental demand. This is a collective response, involving metabolic, mechanical, electrical, and structural alterations, and is known as cardiac plasticity or remodelling. It forms the basis of heart physiology and underlies progression to pathology. Understanding the drivers of re-modelling and the responsible pathways opens therapeutic frontiers by allow-ing direct manipulation of mediators. This is particularly important in contemporary therapeutic cardiology, which predominantly uses treatments directed at the peripheral systems (e.g. kidneys, adrenal glands) and does not immediately solve the problem of the system in question (i.e. heart). This review focuses on the effects of different haemodynamic loads on myocardial phenotype. We ex-amine mechanical scenarios of pressure- and volume overload, temporally tracked in time, from the inciting insult, to compensated, and ultimately de-compensated stage. We discuss how different haemodynamic conditions can result in heterogeneity in clinical presentation and experimental findings. By comparing these we advocate that initial response to load is characterised by phenotypic divergence whereas progression of disease favours convergence to common phenotypes. Finally, we end the review by exploring how current basic cardiac research should leverage available cardiac models to study mechanical load.